2019
DOI: 10.12688/f1000research.18063.1
|View full text |Cite
|
Sign up to set email alerts
|

Growth evaluation of several types of energy crops from tropical shrubs species

Abstract: Background: Few species of tropical shrubs potentially produce biomass to replace fossil fuels for heat production and electricity. The aims of this study were to determine the growth and nutrient status of leaves of several types of energy crops from tropical shrub species with NPK fertilizer application. Methods: Randomized block design was used with ten replications of four levels of fertilizer treatment: T0 = 40 g, T1 = 80 g, T2 = 120 g and T4 = 160 g per plant. Results: The results indicated that fertiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The study design used a Complete Randomized Block Design, which consisted of five NPK fertilizer treatments, namely 0 g (without fertilizer as a control), 40 g, 80 g, 120 g, and 160 g respectively with 3 blocks, every 10 replications and total are 150 plants. Fertilization was done two weeks after planting with commercial NPK fertilizer by YARA, Oslo Norway: N (16%), P (16%), K (16%), Mg (1.5%) and 5% Ca (5%) (Susanto et al 2019a).…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The study design used a Complete Randomized Block Design, which consisted of five NPK fertilizer treatments, namely 0 g (without fertilizer as a control), 40 g, 80 g, 120 g, and 160 g respectively with 3 blocks, every 10 replications and total are 150 plants. Fertilization was done two weeks after planting with commercial NPK fertilizer by YARA, Oslo Norway: N (16%), P (16%), K (16%), Mg (1.5%) and 5% Ca (5%) (Susanto et al 2019a).…”
Section: Experimental Designmentioning
confidence: 99%
“…Study conducted by Payne (2011) showed no effect between plant spacing and plant height, wet weight, and dry weight of V. amygdalina plants. Susanto et al (2019a) reported that at the age of 6 months after planting, several types of tropical shrub plants accumulated a lot of potassium, followed by nitrogen and phosphorus in the leaves. Kemka-Evans et al (2014) reported that epidermal characters are of taxonomic importance in the classification and delimitation of the four taxa among the three species of Vernonia.…”
Section: Growth Characteristics Of Vernonia Amygdalinamentioning
confidence: 99%
See 1 more Smart Citation
“…High nutrient productivity is influenced by long nutrient retention indicated with the high productivity for agriculture capacity, yet it only happened on fertile soil (Hiremath et al 2002). Susanto et al (2019) reported that the accumulation of nutrients in the leaves of the tropical shrub plants varied widely, nitrogen 1.4-2.18%, phosporus 0.11-0.28%, potassium 0.44-2.98%.…”
Section: Effect Of Goat Manure On the Survival Rate And Growth Of M mentioning
confidence: 99%